AKSELERASI LEGALITAS USAHA MIKRO KECIL DAN MENENGAH (UMKM) MELALUI PROGRAM PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) DI DESA MLANDINGAN KABUPATEN SITUBONDO - M. Munir; Nur Muhammad; Nuri Ma'rifatul Laily; Sri Yuniati; Badrus zaman (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
Business legality is a crucial aspect of Micro, Small, and Medium Enterprise (MSME) development; however, some MSME owners in Mlandingan Village, Situbondo Regency, do not yet possess a Business Identification Number (NIB) due to low digital literacy and limited access to information. This community service initiative aimed to increase NIB ownership through awareness-raising programs and community-based registration assistance. The activities involved observation, interviews, Focus Group Discussions (FGDs), and direct assistance provided to eight MSME owners selected through purposive sampling. The assistance focused on the NIB registration process via the Online Single Submission (OSS) system and fostering an understanding of the importance of business legality. The results showed that all participants successfully obtained their NIBs. Furthermore, the participants' perceptions of business legality shifted; what was previously viewed as complicated and unimportant came to be seen as a strategic necessity for business development. The program's success was underpinned by a trust-based approach leveraging social networks and local Islamic educational institutions. This initiative demonstrates that participatory, community-based assistance is effective in enhancing MSME business legality at the village level.